Czym był filozoficzny sceptycyzm i kto był sceptykiem? - Drozdowicz, Zbigniew (Wydawnictwo Fundacji Humaniora, 2016)
In these remarks I attempt to answer the question in the title by recalling several examples of scepticism from the past. Their aim is not just to present its diverse forms but also to prove that first of all radical scepticism was hard to defend (what generated among others the emergence of more moderate forms) and secondly that scepticism situated itself not just in the sphere of ideas but also behavior and in each of them it had its own specific forms of expression. I do hope hover that this presentation of scepticism and sceptics might in some extent lead to a removal of selected misunderstandings related to this philosophical current.
Keywords: philosophical scepticism; radical scepticism; eclectic scepticism; modern scepticism